2023
DOI: 10.1007/s00429-023-02636-9
|View full text |Cite
|
Sign up to set email alerts
|

Representational formats of human memory traces

Abstract: Neural representations are internal brain states that constitute the brain’s model of the external world or some of its features. In the presence of sensory input, a representation may reflect various properties of this input. When perceptual information is no longer available, the brain can still activate representations of previously experienced episodes due to the formation of memory traces. In this review, we aim at characterizing the nature of neural memory representations and how they can be assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 192 publications
1
3
0
Order By: Relevance
“…In support of the emotion-facilitated integration, our imaging results showed that emotional information increased hippocampal reactivation of related memories during both encoding and retrieval. Consistent with emerging work using MVPA to study human episodic memory (Heinen et al, 2023;Hennings et al, 2022;Staresina et al, 2012;Xue et al, 2010), our findings of emotionally-charged increases in reactivation reflect trial-specific reinstatement (i.e., pair-specific similarity) controlling for a general category-level representation (i.e., across-pair similarity). Given the benefits of hippocampal pattern completion on integrative encoding (Kuhl et al, 2010;Shohamy and Wagner, 2008;Wong et al, 2019), the increased hippocampal reactivation of first neutral memories during encoding of second emotional associations could facilitate online integration by rapidly linking neural representations of related information.…”
Section: Emotion-facilitated Memory Integrationsupporting
confidence: 88%
“…In support of the emotion-facilitated integration, our imaging results showed that emotional information increased hippocampal reactivation of related memories during both encoding and retrieval. Consistent with emerging work using MVPA to study human episodic memory (Heinen et al, 2023;Hennings et al, 2022;Staresina et al, 2012;Xue et al, 2010), our findings of emotionally-charged increases in reactivation reflect trial-specific reinstatement (i.e., pair-specific similarity) controlling for a general category-level representation (i.e., across-pair similarity). Given the benefits of hippocampal pattern completion on integrative encoding (Kuhl et al, 2010;Shohamy and Wagner, 2008;Wong et al, 2019), the increased hippocampal reactivation of first neutral memories during encoding of second emotional associations could facilitate online integration by rapidly linking neural representations of related information.…”
Section: Emotion-facilitated Memory Integrationsupporting
confidence: 88%
“…Categorically, a lasting impression may be made into an object for scientific inquiry to be studied as episodic memory. For example, we can research episodic memories as neural representations, recognizable patterns of brain states that reflect the previously experienced episodes (Heinen et al, 2023). This kind of focus, however, passes over experiential aspects of memory.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Our results suggest that it is not only the degree to which a concept shares features that defines the structured representational space, but also the correlated structure across those features. Memory traces for items which have more shared conceptual features will become more similar to one another through semantisation of the trace, leading to poorer memory performance (Heinen et al, 2023), and increased false memories when items are more closely semantically related (Roediger et al, 2001). This may mean that the reason conceptually distinctive objects are better remembered is because this measure increases for items in less dense areas of semantic space -a space represented in the ventral visual and frontal cortices, and memory traces in less dense representational spaces benefit from reduced interference, in turn supporting the retrieval of that item.…”
Section: The Role Of Conceptual Distinctivenessmentioning
confidence: 99%